2023
DOI: 10.3389/fmicb.2023.1236254
|View full text |Cite
|
Sign up to set email alerts
|

Infant gut microbiota colonization: influence of prenatal and postnatal factors, focusing on diet

Clara Suárez-Martínez,
Marina Santaella-Pascual,
Genoveva Yagüe-Guirao
et al.

Abstract: Maternal microbiota forms the first infant gut microbial inoculum, and perinatal factors (diet and use of antibiotics during pregnancy) and/or neonatal factors, like intra partum antibiotics, gestational age and mode of delivery, may influence microbial colonization. After birth, when the principal colonization occurs, the microbial diversity increases and converges toward a stable adult-like microbiota by the end of the first 3–5 years of life. However, during the early life, gut microbiota can be disrupted b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 175 publications
1
8
0
Order By: Relevance
“…In addition, some factors could impact on gut microbiota in infants, such as feeding mode and delivery method. 24 Studies showed that gut microbiota profile in vaginally delivered infants resembled the vaginal microbiota in their mothers, while C-section born infants harboured the gut microbiome more resemble as those of the maternal skin or the environment. 25,26 Another system review indicated that certain bacterial genera (such as Bifidobacterium and Bacteroides) seems to be significantly associated to the mode of delivery in the first 3 months after birth; however, the observed significant differences disappeared after 6 months of age of the infants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some factors could impact on gut microbiota in infants, such as feeding mode and delivery method. 24 Studies showed that gut microbiota profile in vaginally delivered infants resembled the vaginal microbiota in their mothers, while C-section born infants harboured the gut microbiome more resemble as those of the maternal skin or the environment. 25,26 Another system review indicated that certain bacterial genera (such as Bifidobacterium and Bacteroides) seems to be significantly associated to the mode of delivery in the first 3 months after birth; however, the observed significant differences disappeared after 6 months of age of the infants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some factors could impact on gut microbiota in infants, such as feeding mode and delivery method 24 . Studies showed that gut microbiota profile in vaginally delivered infants resembled the vaginal microbiota in their mothers, while C‐section born infants harboured the gut microbiome more resemble as those of the maternal skin or the environment 25,26 .…”
Section: Discussionmentioning
confidence: 99%
“…To date, the pathogenesis of NEC is considered multi-factorial, with the disturbance of normal intestinal flora and overgrowth of potentially pathogenic bacteria implicated in its development. The maternal microbiota serves as the initial microbial inoculum for the infant gut, and perinatal factors such as diet and antibiotic use during pregnancy, as well as neonatal factors like intra-partum antibiotics, GA, and mode of delivery, can influence microbial colonization ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it was widely accepted that birth was the initial opportunity for the mother’s microorganisms to colonise the infant’s gut and influence the immune system [ 66 ]. However, recent findings have revealed that this interaction between the maternal microbiota and the infant’s immune system begins considerably earlier during pregnancy due to the presence of gut microorganisms in the placenta, amniotic fluid, and foetal membranes [ 67 , 68 , 69 ]. Research has demonstrated that the mother’s nutritional status plays a pivotal role in the developmental programming and alteration of the risk of non-communicable diseases in their offspring through epigenetic modifications [ 70 ].…”
Section: Impact Of Maternal Microbiota On Foetal Immune System Develo...mentioning
confidence: 99%